Bioencapsulation of erythromycin using adult brine shrimp, Artemia franciscana (Latreille) - T J. Majack; M B. Rust; K C. Massee; . G. W. Kissil; R W. Hardy; M E. Peterson (Journal of Fish Diseases, 2000)
Live adult brine shrimp, Artemia franciscana (Latreille), were enriched with erythromycin to determine if Artemia could accumulate therapeutic levels for subsequent feeding to young fish. Three trials were conducted to determine the erythromycin incorporation and survival rates of enriched Artemia when fed either liposomes containing erythromycin or various erythromycin suspensions. Erythromycin concentration in Artemia fed a liposome suspension was low (∼ 5 μg mL −1 ) relative to Artemia fed the direct suspension (> 100 μg mL −1 ) over the same time period. When enriched with suspensions up to 1 g erythromycin L −1 sea water for 14 h, Artemia survival was not significantly affected ( P > 0.05) relative to controls. Using a suspension of 1 g L −1 , tissue erythromycin concentrations of 109 ± 16 μg erythromycin mL −1 Artemia homogenate (mean ± SEM) were achieved after 12 h. Concentrations above 170 μg mL −1 were obtained using suspensions of 2–5 g L −1 , but Artemia survival significantly ( P